2014
DOI: 10.7120/09627286.23.1.095
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Welfare Quality® in UK assurance schemes: evaluating the challenges

Abstract: This paper presents an account of a Welfare Quality® assessment of 92 dairy farms carried out by seven experienced assessors. The aim was to evaluate the potential of the Welfare Quality® assessment protocol with respect to its uptake by UK farm assurance schemes. Data collection, and measure aggregation were performed according to the Welfare Quality® protocol for dairy cows. This study examined the data itself, by the testing of how hypothetical interventions might be reflected in changes in the aggregated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
7
31
6
Order By: Relevance
“…The collection of the data used in this paper, along with a list of the measures and any missing values associated with those measures, has been previously described in Heath et al (2014). Briefly, full Welfare Quality ® assessments were carried out on 92 dairy farms located in England and Wales.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The collection of the data used in this paper, along with a list of the measures and any missing values associated with those measures, has been previously described in Heath et al (2014). Briefly, full Welfare Quality ® assessments were carried out on 92 dairy farms located in England and Wales.…”
Section: Data Collectionmentioning
confidence: 99%
“…Data were collected by seven employed assessors who had received standardised training in the Welfare Quality ® assessment protocols. Inter-assessor reliability testing of the assessors was conducted, and is described in Heath et al (2014). The assessments took place between January and August 2011, each by an individual assessor during a single farm visit, immediately after morning milking, according to the protocol guidelines.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as it has been shown that there is no strong association between different welfare indicators (Heath et al, 2014) it is likely that it could only be used for a single welfare indicator and may be best suited as part of a targeted lameness surveillance scheme. Second, a challenge posed by welfare outcome-based assessment in general, is the assumption of random sampling.…”
Section: Discussionmentioning
confidence: 99%